2017
DOI: 10.18203/2320-1770.ijrcog20170575
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal hysterectomy: analysis of clinico-histopathological correlation in Western Rajasthan, India

Abstract: Background: Hysterectomy is the most common gynecological surgery done in the females worldwide as it provides definitive cure to a wide range of gynecological diseases, both benign and malignant. The indications to perform this major surgery should always be justified and the pathology should be proved histopathologically. Histopathological analysis and review is mandatory to evaluate the appropriateness of the hysterectomy.Methods: A retrospective, longitudinal study was conducted in the Department of Obstet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 4 publications
6
7
0
Order By: Relevance
“…6 In this study, the most common preoperative diagnosis for hysterectomy was leiomyoma uterus found in 105 (51.72%) patients followed by ovarian tumor in 34 (16.75%) patients which were similar to the results reported by Acharya S. 7 Jha R. found that leiomyoma was the indication in 24.9%, ovarian tumor in 14.9%, and DUB in 7.7% of the cases. 10 Similar results were observed in the studies done by Yadav DP, Jaleel R and Naheed K. 2,3,9 In our study, the most common histopathological diagnosis was leiomyoma, found in 87 (42.86%) patients, as similar to other studies. 2,4 Ovarian tumor observed in 35 (17.24%) patients was the next common pathology found in this study whereas adenomyosis was also the next common pathology found in other studies.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…6 In this study, the most common preoperative diagnosis for hysterectomy was leiomyoma uterus found in 105 (51.72%) patients followed by ovarian tumor in 34 (16.75%) patients which were similar to the results reported by Acharya S. 7 Jha R. found that leiomyoma was the indication in 24.9%, ovarian tumor in 14.9%, and DUB in 7.7% of the cases. 10 Similar results were observed in the studies done by Yadav DP, Jaleel R and Naheed K. 2,3,9 In our study, the most common histopathological diagnosis was leiomyoma, found in 87 (42.86%) patients, as similar to other studies. 2,4 Ovarian tumor observed in 35 (17.24%) patients was the next common pathology found in this study whereas adenomyosis was also the next common pathology found in other studies.…”
Section: Discussionsupporting
confidence: 91%
“…This finding was similar to previous studies. [2][3][4][5][6][7] In the present study, the maximum number of 110 (54.19%) patients was seen with parity 2-3 which was comparable to other studies. 3,8 The most common clinical symptom in this study was menorrhagia found in 67 (33.00%) patients followed by pain abdomen in 62 (30.54%) patients which were similar to the studies done by Jaleel R, Perveen S and Naheed K. 2,6,9 It is well known that hormonal disturbance in the perimenopausal age group, results in symptomatic menstrual changes.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations